Children's and adults' needs for open space in Tehran's high-rise apartments - Sharghi, Ali (2014)
Dramatically increasing urbanization and population growth bring pressure on open space within urban areas, and the issue has affected lives of urban dwellers. In the process, significant quantities of natural resources or greenery in the urban areas have declined. Nevertheless, significant evidences from research show that contact with nature via open spaces is important for city dwellers, especially children. It is argued that children's relationship with nature is a fundamental to developing their full potential. Previous research also shows lack of playing spaces close to their urban homes and parent-limited opportunity to play outdoors. The situation has resulted less active children, lack of access to open spaces and less mobility in playing places. Lack of connection between children and nature has a physiological and psychological effect on children. Therefore, this study looks into the issue of high-rise open spaces and specifically tries to answer research questions related to adults’ and children’s needs from their high-rise apartments’ open spaces. Two highrise apartments, Sobhan and Pas in Tehran, were selected as study areas; adult’s and children’s needs from their open spaces were gauged by survey, interview and observation. Altogether, 261 adults have been surveyed and 80 children were interviewed. The results of the analysis show that parents and children have differences and similarities regarding their needs from open space. Children show high satisfaction of their needs from open spaces and would like to play in open space and playgrounds because they feel that these areas allow them a wide range of opportunities that are not possible in other areas such as playfield and social spaces. Meanwhile, adults have lower satisfaction from open spaces due to their anxiety for safety in open space. In this relation, compared to children, adults were found to prefer social and formal recreational areas in the open spaces. Regarding the similarity in their preferences, both children and adults like soft landscape's elements such as trees and shrubs. The main implication of this research is that landscape architecture education should be tailored towards understanding users’ needs in order to design open spaces in general. It is also expected that landscape designers try to design high-rise apartments open spaces based on users’ needs, especially related to adults’ and children's preferences and perceived safety. Designers also have to find ways that can enhance familiarity with open spaces. Furthermore, designers are up to challenge to design open spaces in high-rise apartments that capable to combine adults’ and children’s needs for their spaces and activities. In addition, policy and guidelines must be rectified by governments in relation to the planning and design of high-rise apartments open spaces.